Monitoring Effects of Tetracycline and Spectinomycin Perturbations on Biogas Production and Microbiome Dynamics in a Batch Mesophilic Anaerobic Digester - Rani J.; Stablein M.J.; Patel K.; Pang X.; Lahiri P.; Bhalerao K.D.; Dhoble A.S. (My University, 2025)
The microbiomes play a key role in anaerobic digestion (AD) and perturbations caused by external factors like antibiotics may disturb the microbial community dynamics. This experimental investigation studied the effect of antibiotics tetracycline and spectinomycin individually and in combination at three different concentrations on the biogas, methane yield, and microbial dynamics of AD. In a limited 5 days, well-controlled, lab-scale, batch, mesophilic anaerobic digestion experiment, high concentration of spectinomycin impacted the AD process most negatively by yielding 55.13% less methane and 54.02% less biogas followed by 47.12% less methane and 38.31% less biogas in its medium concentration as compared to the control group. High concentration of combination of antibiotics least negatively impacted the biogas (12.52% decrease), and low concentration of tetracycline resulted in the least reduction of 15.17% in methane production. Flow cytometry fingerprinting has been explored as a rapid, high-throughput, objective, data-driven approach to monitor the day-to-day changes in microbial community fingerprints. Dissimilarity variations were observed from day 1 to 5 in autocorrelations data which putatively accounted for the changes in biogas production. This effective monitoring might help in improved AD operation with increased bioenergy yield and prevent the entry of antibiotics and other harmful pollutants into the food chain. © The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature 2023.